Collagen gene expression in human cancer - Fenhalls, Gael (Division of Medical Biochemistry and Structural Biology, 2018)
Type I collagen is the predominant collagen within the stroma and plays an important role in the processes of tumour cell invasion and metastasis during which the collagens within the stroma is degraded. Total RNA was extracted from different stages of breast cancer and adjacent normal tissue for analysis of collagen gene expression by Northern blot hybridisation. Stage I breast tumours had increased α1(I) and α2(I) collagen mRNA, whereas stages II and III tumours had decreased mRNA levels when compared to the adjacent normal tissue. This stage-specific change in collagen gene expression was confirmed by non-radioactive in situ hybridisation and the results indicated that α1(I) and α2(I) collagen mRNA was produced by the stromal fibroblasts and not the tumour cells. To determine whether this altered collagen gene expression was manifested in other cancers, α1(I) and α2(I) collagen mRNA levels were analysed in colorectal carcinoma samples by in situ hybridisation. Colon cancer as in the case of breast cancer, also showed stage specific changes in collagen gene expression. Dukes C and D colon cancer samples had decreased collagen mRNA levels compared to Dukes A and B. Mutated Ras has been shown to affect collagen mRNA levels in vitro (Slack et al, 1992), therefore the colon samples were analysed for Ras mutations in an attempt to correlate Ras mutations with the decreased levels of α1(I) and α2(I) collagen mRNA. Colorectal DNA samples were screened for Ras mutations by SSCP and direct sequence analysis. No possible association was found between the presence of Ras mutations and the decreased collagen gene expression. To gain greater insight into exactly how tumour cells modulate the collagen produced by normal fibroblasts, primary breast fibroblasts (prepared from breast tissue) were cocultured with various breast tumour cell lines. The fibroblasts were also incubated with conditioned media prepared from the tumour cells. Collagen production was analysed using the collagenase assay and the results showed that co-cultured tumour cells, as well as growth in the presence of tumour cell conditioned media, resulted in decreased type I collagen production by the fibroblasts. Type III collagen is often produced in conjunction with type I collagen and we have found that the breast tumour cells modulated type III collagen in the same way as type I collagen. These results demonstrated that a factor(s) was secreted by the tumour cells which affected collagen production. This factor was further shown to stimulate the fibroblasts to produce type I collagenase as analysis of the medium from co-cultured fibroblasts and tumour cells indicated the presence of collagenases. The tumour cell conditioned media was subsequently shown by Western blot analysis to contain a protein of similar molecular weight to the tumour cell derived collagenase stimulatory factor (known as EMMPRIN or extracellular matrix metalloproteinase inducer) which stimulates fibroblasts to secrete collagenases and has been shown to play a crucial role in tumour invasion (Biswas 1982, 1984 and Biswas et al, 1995). In order to determine whether fibroblasts of different origins reacted similarity when cocultured with breast tumour cell lines, WI-38 lung fibroblasts and FGo skin fibroblasts were co-cultured with breast tumour cells. WI-38 fibroblasts responded in the same way as breast fibroblasts (having decreased collagen production), FGo fibroblasts had no effect or slightly elevated collagen production, depending on the tumour cell line. These results suggested that the response to tumour cells is tissue specific. The decrease in type I collagen produced by the fibroblasts when incubated with the tumour cell conditioned media was not due to a decrease in α1(I) and α2(I) collagen mRNA as shown by Northern hybridisation. Type III collagen mRNA was affected differently, the levels were either decreased or increased depending on the tumour cell line being used. We postulate that the fibroblasts and tumour cells required contact for type I collagen mRNA to be decreased. Northern hybridisation showed that types I and III collagen mRNA levels were decreased when tumour cells were co-cultured with the fibroblasts. To demonstrate that specific contact was in fact required, the tumour cells were separated from the fibroblasts by a diffusible membrane and the levels of collagen mRNA were not adversely affected. Tumour cells, therefore can modulate collagen production by normal fibroblasts in two ways I); cause the fibroblasts to secrete collagenases which will degrade the collagen and 2); decrease collagen mRNA. Both of these mechanisms would aid the tumour in invasion and metastasis.